Prolonged, recurrent, spontaneous massive gluteal and femoral bleeding in a patient with five metachronous primary malignancies: Dolgotrajne, ponavljajoče, spontane, masivne krvavitve v zadnjičnem in stegneničnem področju pri pacientu s petimi primarnimi malignomi, nastalimi v različnih obdobjih - Čretnik, Andrej; Šumer, Pia; Breznik, Silva (Acta Medico-Biotechnica, 2023)
Purpose: This study aimed to present the case of prolonged, recurrent, spontaneous massive bleeding in a patient with five metachronous primary malignancies.Case presentation: A 70-year-old male patient presented with massive hematomas in the gluteal and femoral regions and a 6-year  history of prostatic, urethral (penile), right colonic, and right pulmonary carcinoma, with a myeloproliferative disease that recently ended with lymphatic leukemia. Fasciotomies with the evacuation of massive hematomas were performed due to the development of compartment syndrome, which were followed by persistent recurrent bleeding. Despite several surgical interventions with packing, local hemostatic agents and sutures, and selective embolization with immediate clinical discontinuation of bleeding, the digital subtraction angiography showed recurrent bleeding from the peripheral branches of the internal iliac and deep femoral arteries always a few days after the procedures. The coagulation and aggregation parameters and bleeding disorders tests were within normal ranges. The histology showed no malignancy in the affected regions, and no relapse was reported in any regions with previously operated malignant diseases on control computed tomography and positron emission tomography scans.Conclusion: We could stop the bleeding only with more aggressive, nontarget gradual embolization. Subsequently, hemostasis was achieved, with gradual healing of incisions.
Keywords: embolization, massive bleeding, metachronous neoplasms, multiple primary malignancies